2019
DOI: 10.2147/idr.s209881
|View full text |Cite
|
Sign up to set email alerts
|

<p>The increasing threat of silver-resistance in clinical isolates from wounds and burns</p>

Abstract: Purpose The widespread use of silver-containing compounds has led to emergence of silver-resistant bacteria. Few studies are available on the detectability of plasmid-mediated silver-resistance in developing countries. Therefore, we aimed to detect silver-resistance in isolates from wounds and burns, and to genetically characterize plasmid-mediated silver-resistance genes ( sil genes). Methods One hundred and fifty clinical isolates were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…The silver dressing acted least effective against the E. coli and E. cloacae strains. It may be due to the widespread use of silver-containing compounds, which led to the emergence of silver-resistant strains of these species, as was observed by Hosny et al [ 197 ]. Interestingly, staphylococcal strains displayed relatively high sensitivity (compared to other species analyzed) to silver cations, although these microbes are also ubiquitous opportunistic pathogens, constantly exposed to silver in a nosocomial environment.…”
Section: Discussionmentioning
confidence: 96%
“…The silver dressing acted least effective against the E. coli and E. cloacae strains. It may be due to the widespread use of silver-containing compounds, which led to the emergence of silver-resistant strains of these species, as was observed by Hosny et al [ 197 ]. Interestingly, staphylococcal strains displayed relatively high sensitivity (compared to other species analyzed) to silver cations, although these microbes are also ubiquitous opportunistic pathogens, constantly exposed to silver in a nosocomial environment.…”
Section: Discussionmentioning
confidence: 96%
“…Ellis et al concluded in their study that P. aeruginosa was able to develop resistance to silver nanoparticles while S. aureus and A. baumannii did not develop resistance to silver nanoparticles [28]. Hosny et al detected plasmid-mediated silver resistance in clinical bacteria like P. aeruginosa, A. baumannii and S. aureus isolates [29]. Results from Kaweeteerawat et al study suggested that silver nanoparticles enhanced the bacterial resistance to antibiotics by promoting stress tolerance through induction of intracellular ROS [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hosny et al. detected plasmid-mediated silver resistance in clinical bacteria like P. aeruginosa, A. baumannii and S. aureus isolates [ 29 ]. Results from Kaweeteerawat et al.…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial species usually exert a damaging effect on wound healing ( 15 , 33 ). Many other species of bacteria in chronic wounds have also been reported, including Enterobacter cloacae ( 17 , 34 36 ), Citrobacter sp. ( 37 , 38 ), Peptostreptococcus sp.…”
Section: Discussionmentioning
confidence: 99%